Flexing the frame: therapist experiences of museum-based group art psychotherapy for adults with complex mental health difficulties. Issue 2 (3rd April 2019) - Coles, Ali; Harrison, Fiona; Todd, Saira
ABSTRACT: This research aimed to investigate our experiences of facilitating museum-based art psychotherapy groups for adults with complex mental health difficulties, identifying key themes to help inform the practice of other art psychotherapists working in museum settings. Drawing on concepts of tacit knowledge, action research, reflexivity and arts-based research, we engaged in structured discussions and reflective art-making in three areas of focus, and then carried out a simple thematic analysis of the data. The areas of focus were: the role of museum objects within the art psychotherapy process; the movement between and within the private artmaking space and the public spaces of the museum; and the potential impact of the public nature of the museum. The themes we identified relate to familiar theoretical concepts such as containment, mentalisation, transitional objects and space, attachment and joint attention. Our research led us to challenge our feeling that we were 'breaking the rules' of 'orthodox' group art psychotherapy practice by working outside the framework of a traditional therapy room. We conclude that there is potential value in this particular way of 'flexing' our practice and encourage other art psychotherapists to explore museum-based work and share their experiences. Plain-language summary This article explores the issues involved in running art psychotherapy groups for people with long term mental health difficulties in museums instead of NHS outpatient centres. It is written from the perspective of three art psychotherapists who examine their own experience of running these types of groups. The research gives insights into the opportunities and challenges of working in this way. We started by agreeing on three specific questions: what significance might the museum objects hold for the service users, how might physically moving between a private art-making room and the public space of the museum impact on the service users, and what are the potential issues involved in delivering art psychotherapy in a public building rather than the more private space of an NHS building? For each of the three areas we met twice. At the first session we discussed our experience of running the museum-based groups in relation to that area, and at the second we used artmaking to expand our discussion. We recorded and transcribed our discussions and analysed the transcripts. The analysis produced several themes, which we then related to existing psychotherapeutic theory. We used a simple research process that helped us to think about what we do as art psychotherapists and why - a process which other art psychotherapists could use for their own research. We conclude that there are different issues and opportunities when working in museums compared with working in NHS buildings. The work challenges traditional expectations of how art psychotherapy is carried out and requires creativity and flexibility on the part of the therapist. We found that using museums for art psychotherapy was an interesting and valuable extension to our work. Other art psychotherapists who wish to run groups in museums may find our insights useful.